Measuring Spontaneous Focus on Space in Preschool Children - Perez, Jasmin; McCrink, Koleen (Frontiers in Psychology, 2019)
Previous work on children’s Spontaneous Focus on Numerosity (SFON) has shown the value of measuring children’s spontaneous attention within naturalistic interactions. SFON is the spontaneous tendency to focus attention on, and explicitly enumerate, the exact number of items in a set. This measure predicts later math skills above and beyond general IQ and other cognitive factors such as attention. The utility of SFON suggests that a parallel construct for space is a worthy pursuit; spatial cognition underlies many of our mathematical skills, especially as children are first learning these skills. We developed a measure of children’s Spontaneous Focus on Space - the spontaneous tendency to attend to absolute and relative spatial components of the environment - and studied its relation to reasoning about the important spatial-numerical concept of proportions. 55, 3-6-year-olds were tested at a local children’s museums in New York City. Children participated in tasks designed to measure their spontaneous focus on space and number, and their ability to reason about spatial proportions. Results indicate that as children grow older, their Spontaneous Focus on Space becomes more complete and is positively related to proportional reasoning performance. These findings suggest that spatial awareness is rapidly increasing in the preschool years, alongside numerical awareness and spatial-numerical proportional reasoning.